The mists of Eden nature's last paradise - Sherman, Erica (Kansas City, Mo. : Landmark Editions, 1998)
The rainforest, nature's last paradise, speaks of its waters, its plants and animals, and its struggle to survive being destroyed by people.
4 - 8 years
Keywords: Rain forests -- Juvenile poetry; Nature -- Juvenile poetry; Children's poetry, American; Rain forests -- Poetry; Conservation of natural resources -- Poetry; American poetry